The lateral load carrying capacity of wall ties used in cavity wall construction in the Western Cape : a comparison between the Butterfly-type wire tie and the Crimped-type wire tie - Ebrahim, I (Department of Civil Engineering, 2014)
Bibliography: leaves 69-71.